Application of “One Syndrome and One Produce” model in the management of chronic and refractory skin ulcer in the “Yanjing Ulcer Healing” workshop (“一证一品”建设模式在“愈疮工坊”慢性难愈性溃疡管理中的应用) - SHI Chunhong (石春红); XIE Ran (谢冉); HAO Li (郝丽); YUE Lina (岳丽娜) (中西医结合护理)
Beijing Hospital of Traditional Chinese Medicine Affiliated to Capital Medical University had lunched the project of “One Syndrome and One Produce” specialized nursing demonstration ward and achievements had been made after first three-year interval of implementation. A characteristic nursing service, "Yanjing Ulcer Healing” Workshop", was created and efforts were made to explore the ways of improving the quality of specialized nursing for patients with chronic refractory ulcer. The establishment of “One Syndrome and One Produce” mode is to provide professional and homogeneous nursing services for patients, and improve patients' medical experience. This paper summarized the construction process and achievements of the“ One Syndrome and One Produce” nursing project. (北京中医医院疮疡科落实北京市中医药管理局提出的“一证一品”专科护理示范病房建设项目, 通过3年的建设周期取得一定成果。打造特色护理服务品牌“燕京疮疡-愈疮工坊”, 对提高慢性难愈性溃疡专科护理质量管理模式进行了新的探索和实践, 使患者获得专业化、同质化护理服务, 达到提升患者就医体验的目的。本文就项目建设过程及成果进行经验总结。)